Moth community responses to woodland creation: The influence of woodland age, patch characteristics and landscape attributes. (2nd August 2022) - Fuentes‐Montemayor, Elisa; Watts, Kevin; Sansum, Philip; Scott, Will; Park, Kirsty J.
Abstract: Aim: Large‐scale habitat creation is crucial to mitigate the current ecological crisis, but scientific evidence on its effects on biodiversity is scarce. Here, we assess how assemblages of a biodiverse group (moths) develop over time in habitat creation sites. We use temperate woodlands as a case study, and compare species assemblages in restored and mature habitat patches. We also identify local‐ and landscape‐level attributes associated with high species richness and abundance. Location: Central Scotland, United Kingdom. Methods: We surveyed moths in a chronosequence of 79 temperate woodland patches encompassing woodland creation sites (20–160 years old) and mature "ancient" woodlands (250+ years old). We used structural equation models, generalized linear models and ordination techniques to quantify moth community responses to woodland creation, and degree of similarity to moth assemblages in ancient woodlands. Results: Woodland creation sites harboured large numbers of moth species (212), were dominated by woodland generalists and had high species turnover. Moth abundance and diversity increased with woodland connectivity. Macromoths were more abundant and diverse in younger woodlands; micromoth specialists occurred more frequently in older woodland creation sites. Ancient woodlands had similar moth abundance/richness than woodland creation sites (except for fewer macromoth woodland specialist species), but their species composition was somewhat different. Patterns of beta diversity (low nestedness) indicated that moth species in woodland creation sites are not simply subsets of species in ancient woodlands. Main conclusions: To benefit moth communities, woodland creation sites should be structurally diverse and in close proximity to other woodlands. At the landscape scale, a mosaic of woodland patches of different ages is likely to increase moth beta (and consequently gamma) diversity. Ancient woodlands and woodland creation sites each host substantial proportions of "unique" species; individual woodland patches contain distinctive moth assemblages and should be protected and valued for their contribution to regional moth diversity.